AWARENESS ABOUT THE HOMER OR THE SUBJECTIVE AND COGNITIVE ASPECTS OF THE PROBLEM (ResearchJet Journal of Analysis and Inventions, 2021)
The article tells the story and literary credo of the Russian poet V.A. Zhukovsky, who translated part of Homer's “Iliad” into Russian. He was known in the eyes of his contemporaries as the owner of the most advanced worldview. He was a renowned teacher, poet and translator, well acquainted with the works of German thinkers and philosophers.